Effectiveness Bleaching of Waste Cooking Oil Cleaning Using Nano-Montmorillonite Adsorbent - Silvia Ningsih; Puji Wahyuningsih; Tisna Harmawan (Elkawnie: Journal of Islamic Science and Technology, 2022)
Abstract: Waste cooking oil contains carcinogenic compounds which are formed during the frying process. The content change makes it is not worth for reuse cooking oil. One of the damages to cooking oil is caused by heating. The quality of useable oil refers to SNI 01-3741-2013. The sample used in this research is waste cooking oil that is used for 5 times of frying. The quality of the oil can be improved using Nano-Montmorillonite adsorbent. The results of PSA and FTIR characterization show that Nano-Montmorillonite has a nano-scale particle size of 15.3 nm with a percentage of 6%. The rest are particles that have a size> 100 nm with a total percentage of 94% with a respective size of 383.9 nm with a percentage of 59% and 6647.1 nm with a percentage of 35% and have functional groups, namely hydroxyl (-OH), Si-O-Si and Al-Al-OH. Testing of waste cooking oil quality includes organoleptic, acid numbers, peroxide numbers, and saponification numbers using Nano-Montmorillonite. Based on the results, the more Nano-Montmorillonite adsorbent was added, the lower the numbers of acid, peroxide, and saponification in waste cooking oil and the better the quality of flavor and color. Based on this analysis, Nano-Montmorillonite adsorbent can improve the quality of waste cooking oil.